Joyce, Steinberg, and Acher: A Literary Analysis on the Consciousness of Heresy - Berman, Shmuel (Iggrot Ha’Ari, 2022)
The heretic is a commonly portrayed figure in both religious and non-religious works, and the particulars of their character are defined by the author’s religious context. This essay contrasts the heretic figures in the Talmud, Milton Steinberg’s As A Driven Leaf, and James Joyce’s Portrait of the Artist as a Young Man. These characters’ actions and beliefs reveal how broad the category of heresy is and how its definition is deeply relative to the culture from which it sprouts.